2004
DOI: 10.1103/physrevlett.93.200801
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Imaging of Single Fluorescent Molecules with the Optical Near-Field of a Metal Tip

Abstract: We show that a concentration of light at a metal tip allows near-field optical imaging of single fluorescent dye molecules at very high resolution, despite strong quenching effects. Details as small as 10 nm were observed in the fluorescence patterns of single Cy-3 dyes bound to the termini of DNA. Data evaluation by model fitting determines the positions of the dyes to an accuracy even better than 1 nm and also yields their 3D orientation. The metal tip simultaneously provides high-resolution topographic imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
182
2
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(198 citation statements)
references
References 22 publications
(26 reference statements)
3
182
2
6
Order By: Relevance
“…8,11,112,[118][119][120][121][122][123] Metallic tips are usually preferred due to their more favorable scattering, confinement, and field enhancement characteristics. 14,105,116,123,124 Some study in the past decade however has shown that silicon tips are a promising solution for achieving the highest resolution with apertureless SNOM due to more capable semiconductor fabrication techniques. 113,125 FIG.…”
Section: Apertureless Snom Probesmentioning
confidence: 99%
“…8,11,112,[118][119][120][121][122][123] Metallic tips are usually preferred due to their more favorable scattering, confinement, and field enhancement characteristics. 14,105,116,123,124 Some study in the past decade however has shown that silicon tips are a promising solution for achieving the highest resolution with apertureless SNOM due to more capable semiconductor fabrication techniques. 113,125 FIG.…”
Section: Apertureless Snom Probesmentioning
confidence: 99%
“…For single particles, the enhanced near-fields are their most important property. Increasing the local intensity on a restricted volume allows for the selective excitation of single fluorescent molecules (Bharadwadj et al, 2007;Frey et al, 2004;Sandoghdar & Mlynek, 1999).…”
Section: Plasmonics -Optical Antennasmentioning
confidence: 99%
“…To overcome these barriers, so-called "tip-enhanced near-fieldopticalmicroscopy"(TENOM)hasbeenintroduced. [24][25][26][27][28] In contrast to aperture-type NSOM, this technique is capable of achieving superior optical resolution, but the application to biological samples in physiological conditions has yet to be demonstrated. The laser-irradiated metal tip employed in TENOM can be viewed as a special type of optical antenna.…”
mentioning
confidence: 99%